Fresno County Bar Association Luncheon with Justice Cruz Reynoso - Watkins, Howard::::::::: (1982)
Audience and head table: JV Henry holding cigarette, Dennis Caeton, Hon. Armando Rodriguez; head table: Leroy Cordova, Thomas Tusan, Doug Jensen, Justice Reynoso, Robert Oliver, Lenore Schreiber